EFFORTS TO IMPROVE THE NUMERATION LITERACY SKILLS OF CLASS V STUDENTS IN KALOY STATE PRIMARY SCHOOL THROUGH CRA METHOD - Sujoko Waluyo (RADJA PUBLIKA, 2025)
This study investigates the application of the Concrete–Representational–Abstract (CRA) method to strengthen numeracy literacy among fifth-grade students at SD Negeri Kaloy. Despite national efforts to improve mathematics education, Indonesia's performance in the Program for International Student Assessment (PISA) remains low, with a score of 366 in 2022, down from 391 in 2006. Such results highlight persistent challenges in students' ability to interpret, analyze, and apply mathematical concepts in real-life contexts. Using a classroom action research (CAR) design, data were collected through observation, tests, and reflective cycles involving 25 students during the 2024/2025 academic year. The study focused on four indicators of numeracy literacy: the use of mathematical symbols, question analysis, interpretation/prediction, and decision-making. The CRA method was operationalized through concrete media (paper cutouts), representational tools (visual models and videos), and abstract notation, tailored to students' diverse learning styles—visual, auditory, and kinesthetic. Findings reveal that CRA significantly improved students' ability to use mathematical symbols and draw accurate conclusions, while challenges persist in auditory learning due to technical limitations in video delivery. Visual and kinesthetic learners demonstrate higher consistency and engagement, underscoring the importance of differentiated instruction. Overall, CRA enhanced conceptual understanding, long-term retention, and numeracy literacy across all indicators. This study concludes that CRA is a relevant and effective pedagogical approach to address Indonesia's numeracy literacy gap. Practical implications include the integration of concrete manipulatives, multimodal learning resources, and reflective cycles into mathematics instruction, offering a scalable model for improving student outcomes in primary education.